Technology Selection of Microalgae Thermochemical Conversion to Bio-Crude Oil - Sutejo, G.; Dewayanto, N.; Suyono, E. A.; Budiman, A. (2022)
Microalgae as a third-generation biofuel source with various advantages is a potential part of renewable energy resources. Various studies on the conversion process of microalgae into biofuels have been carried out, one of which is the thermochemical process. The thermochemical conversion process is considered better than the biochemical process which has a low conversion rate and higher production costs. Recent researches state that to obtain bio-crude oil from microalgae through a thermochemical process, there are two alternative technologies that can be used, which are pyrolysis and liquefaction. In this research, a selection was made to determine which technology was better using decision making tools of Analytic Hierarchy Process (AHP) method. The evaluation criteria that have been used are technological (readiness level, energy efficiency, pre-treatment process, and product output), operational complexity, environment, and economy (investment cost and operation cost). The alternative technologies evaluated were pyrolysis with bubbling fluidized bed reactor, pyrolysis with circulating fluidized bed reactor, and hydrothermal liquefaction. From the results of pairwise comparisons, the technological criteria had the highest weight (0.343) and hydrothermal liquefaction technology was the best alternative technology among other alternatives (0.420). © Published under licence by IOP Publishing Ltd.